DERECHOS LINGÜÍSTICOS Y POLÍTICAS PÚBLICAS - Valer Bellota, Pavel H. (2020)
The United Nations Organization has declared 2019, and the years 2022-2032, as the international year and decade of indigenous languages. A momentous act of the international community that seeks to draw attention to the serious and regrettable loss of cultural and linguistic diversity. The call of the international community assumes special importance in the current conditions of linguistic diversity in postcolonial states. The colonization of America inaugurated the process of the disappearance of the world's languages, a long process that has led to a disastrous scenario.